Significance of Total Quality Management and Doing Right First Time in Promoting Environmental Sustainability - Luis Javier Márquez Figueroa; Jorge Luis García Alcaraz; José Roberto Diaz Reza; Jesús Alfonso Gil López (Memoria Investigaciones en Ingeniería)
This article reports a study that analyzes a structural equation model that relates lean manufacturing tools associated with quality control to the benefits obtained in the maquiladora industry of Ciudad Juarez (Mexico). A questionnaire was designed and administered to the regional industry to obtain information about the implementation levels of Total Quality Management, Doing Right First Time, and environmental sustainability. The variables were related through three hypotheses, validated by empirical information from 176 responses to the questionnaire. The results indicate that the relationship between Total Quality Management and Doing Right First Time is strongest in the model. Sufficient statistical evidence affirms that these tools influence environmental sustainability in the Mexican maquiladora industry. Therefore, it is recommended that top management focus their efforts on quality control to guarantee environmental sustainability, focusing on production systems that make quality products for the first time and reduce waste in the process.